2009
DOI: 10.4319/lo.2009.54.6.1941
|View full text |Cite
|
Sign up to set email alerts
|

Biogeneration of chromophoric dissolved organic matter by bacteria and krill in the Southern Ocean

Abstract: Chromophoric dissolved organic matter (CDOM), the optically active fraction of dissolved organic matter, is primarily generated by pelagic organisms in the open ocean. In this study, we experimentally determined the quantity and spectral quality of CDOM generated by bacterioplankton using two different substrates (with and without photoproducts) and by Antarctic krill Euphausia superba and evaluated their potential contributions to CDOM dynamics in the peninsular region of the Southern Ocean. CDOM was generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 35 publications
5
64
1
Order By: Relevance
“…The microbial production of CDOM has also been observed during microbial culture experiments Biers et al, 2007;Ortega-Retuerta et al, 2009). On the other hand, various biological sources, i.e., zooplankton Ortega-Retuerta et al, 2009), cyanobacteria Trichodesmium spp. , and dinoflagellates (Vernet and Whitehead, 1996) have been considered as sources of CDOM.…”
Section: Factors Controlling the Cdom Level At The Subarctic And The mentioning
confidence: 79%
See 2 more Smart Citations
“…The microbial production of CDOM has also been observed during microbial culture experiments Biers et al, 2007;Ortega-Retuerta et al, 2009). On the other hand, various biological sources, i.e., zooplankton Ortega-Retuerta et al, 2009), cyanobacteria Trichodesmium spp. , and dinoflagellates (Vernet and Whitehead, 1996) have been considered as sources of CDOM.…”
Section: Factors Controlling the Cdom Level At The Subarctic And The mentioning
confidence: 79%
“…At the BATS site in the Sargasso Sea, the seasonal cycle of CDOM level has been considered the result of photobleaching, winter convective mixing, and production during heterotrophic recycling of organic carbon rather than primary production (Nelson et al, 1998;. The microbial production of CDOM has also been observed during microbial culture experiments Biers et al, 2007;Ortega-Retuerta et al, 2009). On the other hand, various biological sources, i.e., zooplankton Ortega-Retuerta et al, 2009), cyanobacteria Trichodesmium spp.…”
Section: Factors Controlling the Cdom Level At The Subarctic And The mentioning
confidence: 86%
See 1 more Smart Citation
“…Within these autochthonous sources, CDOM can be produced as a by-product of DOM metabolism, mainly by bacteria. But its production by copepods, krill, and other planktonic organisms has also been demonstrated in recent studies (Steinberg et al 2004;Ortega-Retuerta et al 2009). …”
mentioning
confidence: 99%
“…Studies have also shown that inefficiencies in the SO bio-optics algorithms is generated from green band reflectance, leading to an obvious underestimation in chlorophyll-a when using global empirical coefficients [9]. In addition, the blue band is highly affected by CDOM, whose absorption coefficient was reported to occupy 70% of the non-water components in WAP (west of the Antarctica Peninsula) [37]. The absorption spectrum of CDOM has decreasing exponential influence, showing less influence on longer bands.…”
Section: Fluorescence Approach Estimation For Chlorophyll-amentioning
confidence: 99%